The effect of metformin on inferior alveolar nerve regeneration following crush-type injury - Gundogdu S.; ÖZYILMAZ Ö.; OLGAÇ N. V.; Miloro M. (My University, 2026)
Peripheral nerve injuries often cause significant sensory and motor dysfunction, but current treatments provide limited neurosensory recovery. Beyond its antidiabetic use, metformin shows promise as a neuroprotective and regenerative agent by modulating autophagy and reducing inflammation. This study aimed to investigate the potential therapeutic effects of metformin on inferior alveolar nerve (IAN) regeneration following crush-type injury in a rat model. Thirty male Sprague–Dawley rats were randomly divided into metformin, placebo, and control groups. A crush injury was performed on the IAN in all but the control group. The metformin group received daily intraperitoneal 5 mg/kg injections for 10 days. Regeneration was assessed on day 28 by histological and immunohistochemical analyses, and functional recovery was evaluated using the von Frey test at day 0 (preoperative baseline) and on postoperative days 1 (T1), 7 (T7), 10 (T10), and 28 (T28). Histologic results showed reduced inflammation, oedema, fibrosis, and degeneration, and greater regenerated nerve fibre density in the metformin group. Immunohistochemical analysis showed a marked elevation in GAP-43 expression in the metformin group compared to the placebo and control groups (P < 0.05). Von Frey results showed gradual improvement in mechanical sensitivity in the metformin group, suggesting better recovery. Metformin showed neuroregenerative effects on crushed IAN in rats by promoting repair, increasing GAP-43, and reducing inflammation. These findings support its therapeutic potential in peripheral nerve injury and warrant further research for clinical application.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Diş Hekimliği; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Dentistry; Health Sciences; Diş Hekimliği Oral Cerrahi ve Tıp; Klinik Tıp (Med); Klinik Tıp; Cerrahi; Dentistry Oral Surgery & Medicine; Clinical Medicine (Med); Clinical Medicine; Surgery; Otorhinolaryngology; Ağız Cerrahisi; Oral Surgery; Crush injuries; Gap-43 protein; Mandibular nerve; Metformin; Nerve regeneration